The beautiful game / Level 2 - Flinders, Steve; Lindop, Christine (Oxford ; New York : Oxford University Press, 2009)
"Some call it football, some call it soccer, and to others it's the beautiful game. By any name, it's a sport with some fascinating stories. There is a game that lasts for two days where many players never see the ball. There's the French writer who learnt lessons about life from playing football, and the women players who had to leave the club grounds because 'Women's football isn't nice'. The cups, the leagues, the World Cup finals, the stars, the rules - they're all a part of the world's favourite sport, the 'Beautiful Game'." -- publisher's website
Stage 2 (700 headwords)
Keywords: Soccer; Readers for new literates; Sports; Graded Reader Level 2; Football